Les femmes noires qui aiment les femmes : résistances aux rapports de pouvoir enchevêtrés - Almeida, Jade (Université de Montréal, 2022)
« Les femmes noires qui aiment les femmes : résistance aux rapports de pouvoir enchevêtrés » aborde les questions de survie d’un point de vue queer et diasporique. Cette thèse soutient que les pratiques et positionnements au quotidien des participantes se situent dans les failles d’un système qui criminalise l’existence même des personnes noir.e.s. L’analyse des conditions de vie de ces femmes permet de mieux comprendre le panorama complexe des systèmes de pouvoir à l’intersection des rapports de classe, de genre, de race et de l’hétéropatriarcat. Elle permet également de reconnaitre leur capacité à créer un espace alternatif, un univers des possibles qui s’oppose aux catégories normatives et hégémoniques. Les réalités des participantes génèrent donc des points de départ où l’altérité devient outil de pensée critique, moyen de résistance et fondement d’un futur substantiellement différent infusé par l’espoir de l’amélioration. Cette recherche se base sur l’autoethnographie, une ethnographie de la participation et des entretiens semi-dirigés de 22 personnes qui s’identifient comme femmes, noires et ayant des rapports sexo-affectifs avec d’autres femmes. Cette thèse porte donc sur le désir et s’appuie sur de multiples apports, majoritairement de théoriciennes racisées, qu’elles soient issues du milieu académique ou fassent partie de mon cercle privé. Elle est formée par de puissants récits, mais également par des silences tout aussi évocateurs, par une attention accrue au domaine du micro et à la description, par une autoethnographie de la participation et par la volonté de dépeindre sur quelques pages ne serait-ce qu’un extrait de la flamboyance de ces femmes.
Accepted: 2022-04-04T18:00:49Z
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; afro-féminisme; amériques; approches et analyses; autoethnographie; canada; communauté; cours; diaspora africaine; discipline; désir; désir lesbien; femmes* noires; féminismes noirs; intersectionnalité; lesbianisme; militance; montréal; point de vue situé; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sexualité; sociologie; thématiques

Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

The movement for reproductive justice: Empowering women of color through social activism - Zavella, Patrica (NYU Press, 2020)
Shows how reproductive justice organizations' collaborative work across racial lines provides a compelling model for other groups to successfully influence change Patricia Zavella experienced firsthand the trials and judgments imposed on a working professional mother of color: her own commitment to academia was questioned during her pregnancy, as she was shamed for having children "too young." And when she finally achieved her professorship, she felt out of place as one of the few female faculty members with children. These experiences sparked Zavella's interest in the movement for reproductive justice. In this book, she draws on five years of ethnographic research to explore collaborations among women of color engaged in reproductive justice activism. While there are numerous organizations focused on reproductive justice, most are racially specific, such as the National Asian Pacific American Women's Forum and Black Women for Wellness. Yet Zavella reveals that many of these organizations have built coalitions among themselves, sharing resources and supporting each other through different campaigns and struggles. While the coalitions are often regional-or even national-the organizations themselves remain racially or ethnically specific, presenting unique challenges and opportunities for the women involved. Zavella argues that these organizations provide a compelling model for negotiating across differences within constituencies. In the context of the war on women's reproductive rights and its disproportionate effect on women of color, and increased legal violence toward immigrants, The Movement for Reproductive Justice demonstrates that a truly intersectional movement built on grassroots organizing, culture shift work, and policy advocating can offer visions of strength, resiliency, and dignity for all.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; afro-féminisme; amériques; anthropologie; approches et analyses; discipline; droits des femmes*; ethnographie; femmes* immigrantes; identités LGBTQIA2+; intersectionnalité; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; sciences humaines; sociologie; thématiques; violences; violences d'état; violences gynécologiques et obstétricales; états-unis

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; afro-féminisme; approches et analyses; care; corps; cours; discipline; fem1000; féminismes noirs; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; émotions; études culturelles

La traduction du black feminism américain en contextes francophones. - Amandine Gay (2016)
À l’occasion de l'arrivée en librairie de la première traduction française du classique afroféministe de bell hooks, Ne Suis-je Pas Une Femme, les éditions Cambourakis et La Centrale Galerie Powerhouse organisent une discussion autour de la traduction du Black Feminism américain en contexte francophone. Modératrice: Amandine Gay Invitées: Leïla Benhadjoudja et Stéphane Martelly
Keywords: 2000 à aujourd'hui; 2010-2019; afro-féminisme; amériques; approches et analyses; cours; discipline; discours dominant; fem3300; féminisme afroaméricain; militance; premier cycle; périodes historiques; québec; racisme; ressource en ligne; régions géographiques; système colonial; systèmes d'oppressions; thématiques; traduction